Para além de uma "incubadora de monstrinhos" : a formação do jovem trabalhador sob a lei da aprendizagem - Soares, Ozias de Jesus (2006)
The present study analyzes the formation of young workers mediated by the Law of the Learning (10.097/00). We search to point out the historicaly the object, having in account the regimen of flexible accumulation and the relations with the current politics of insertion of the young in the world of the work. The research had as empirical field the program of learning called Projeto Mundo do Trabalho , of the not governmental organization São Martinho, in Rio De Janeiro. We analyze the ideologie that strengthen the dual character of the brazilian education, presents nowadays. Among these, we observe the work for adolescents show in the capitalist society as disciplinaizing, maintenance of social order and, therefore, taken as preventive of social diseases. When we analyzes the union proposals between study anda work under the optics of the capital, the professional learning is for that one a speedy and utilitarian insertion, to having in view the market. And for the work, the perspective of this union would be an instrument for the instauration of new relations between manual and intellectual work, having as horizon - from the knowledge of the sphere of the production and the general knowledge - the formation of controllers, of the intellectual of new type. We present, after that, some quarrels in the land of the new model of State of neoliberal contour, ally to the new standard of accumulation. We argue the paper of the calls not governmental organizations in the conduction of the social programs, in special, the direction that assume in its majority, namely, the relief of the poverty and the containment of the social convulsions. Amongst the organizations that work with the child and the adolescent, we detach the paper of the Associação São Martinho, in the conduction of the learning program World of the Work . We could, then, display the form as if it constituted, as much the institution as the project for adolescent apprenticees in this context. We present the empirical field of the research, we relating the interviews and comments with you arrive in port them theoretical used. We dialogue with young and professionals of the program in screen to perceive what world of the work in them presents the educative processes and so that world of the work educates the educative processes in the companies and in the institutions. In spite of contradictions between capital and work that move the relations among work and education in the learning programs, we could identify positivities of the program, surely, not given, but constructed in the daily praxis of young workers above the Law of the Learning.